Multiplex Immunofluorescence Assay of Infiltrating Mononu-Clear Cell Subsets in Acute T-Cell-Mediated Rejection and BK Virus-Associated Nephropathy in the Allograft Kidney - Mee-Seon Kim; Jeong-Hoon Lim; Man-Hoon Han; Sang-Yeob Kim; Yun Jae Kim; Yong-Jin Kim (Diagnostics, 2022)
Renal allograft biopsy is the gold standard procedure for diagnosis of kidney rejection via specific pathological changes. To provide a better assessment of immunologic events in acute T-cell-mediated rejection (acute TCMR) and BK virus-associated nephropathy (BKVAN) cases, we used multiplex immunofluorescence staining to identify infiltrating mononuclear cell subsets in the cortex area of transplanted kidneys. Antibodies to CD4, CD8, CD20, CD68, Foxp3, and cytokeratin were used. In cortical interstitium, CD8+ cells were significantly more prevalent in acute TCMR than BKVAN cases (34% vs. 22.8%, p = 0.034). In medulla, CD20+ cells were significantly more prevalent in BKVAN than acute TCMR cases (51.9% vs. 11.3%, p = 0.028).